Promoting (pro) vitamin A-rich bananas: A chronology - Fongar, Andrea; Nabuuma, Deborah; Ekesa, Beatrice (2020)
Micronutrient deficiencies remain the largest nutritional problem worldwide, with globally over 2 billion people affected. Vitamin A deficiency (VAD) remains a widespread and major public health concern in Africa and South-East Asia. VAD prevalence in Eastern Africa significantly exceeds the WHO threshold of 30%, indicating a severe public health and nutrition problem for the region (Burundi 46%; DRC 64%; Tanzania 43%; Uganda 39%). Besides its role in healthy vision, vitamin A is important for several physiological processes within the human body, including foetal development, immune response, and growth and therefore, is crucial for maternal and child wellbeing and survival. Among the numerous strategies that have been employed in the fight against VAD, reports indicate that food-based strategies are the most sustainable, especially among rural communities who depend on agriculture for both food and income. Thus, this HarvestPlus-supported 14-year-long project, entitled, Addressing micronutrient deficiencies in sub-Saharan Africa through Musa-based foods’ has defined strategies and fast-track deployment mechanisms that increase access to and consumption of high-micronutrient Musa-based foods for micronutrient-deficient populations in sub-Saharan Africa, with a focus on Burundi, Eastern DRC, Tanzania and Uganda. HarvestPlus improves nutrition and public health by developing and promoting new and/or more nutritious varieties of staple food crops that are rich in vitamins and minerals and providing global leadership on biofortification evidence and technology (see https://www.harvestplus.org/content/about). To date, 15 provitamin A-rich banana cultivars of different sub-groups (Plantain, ABB Cooking bananas, AA and AAA Dessert bananas, Pacific Plantains and AA Cooking bananas) from different countries with above-average levels of provitamin A carotenoids (pVAC) (retinol activity equivalents >333μg/100gdw) have undergone agronomic evaluation (3-6 cycles) alongside local cultivars of the same sub-group. Following this activity, seven cultivars namely Apantu-AAB African Plantain (Ghana), Bira-AAB Pacific Plantain (Papua New Guinea), Pelipita-ABB Plantain (The Philippines), Lahi-AAB Pacific Plantain (Hawaii), Lai-AAA Dessert (Thailand), Pisang Papan-AAA Dessert (Indonesia) and Muracho-AAB Plantain (the Philippines), have demonstrated potential to perform well within Eastern Africa. Furthermore, the 15 cultivars have undergone sensory evaluation alongside the local cultivars of similar sub-groups. The cultivars were evaluated as raw, ripe (dessert) fruit, and also following boiling, roasting, frying, and steaming. More than 500 farmer-representatives have been involved and findings indicate that five of the 15 tested cultivars (Apantu, Bira, Lai, Pelipita, To’o) are well accepted and their preference is not statistically different from the local cultivars with acceptability scores ranging from good to very good. Agronomic, sensory and pVAC content evaluation indicates that the best performing cultivars are Apantu, Bira, Lahi, Pelipita, Muracho, and Pisang Papan. Since 2016 efforts have been made to accelerate macro-propagation activities to ensure the distribution of sufficient planting material of the preferred cultivars. More than 17,000 high pVACs banana plantlets have been distributed directly to farmers by the project team and partners. Additionally, farmer-to-farmer sharing of the banana planting materials have been reported. For example, 1,021 plantlets were shared amongst farmers in 2017. The project included capacity building of community members through a training of trainers approach (TOT). Through the 497 community resource persons (291 men and 206 women), that have been trained and equipped with information on the best practices on management of banana plantations, appropriate intercropping, storage techniques, cooking methods and dietary combination, and food safety and hygiene, more than 12,900 farmer-households (5,000 men and 7,900 women) have been reached directly with information on sustainable utilization of the vitamin A bananas in their farming and food systems. Involving community members, nutritious recipes based on the provitamin A-rich bananas combined with beans, fish and other nutritious ingredients have been developed. In collaboration with CIP-Nairobi, samples of the developed recipes were tested to establish their full nutrient composition value. Findings indicated that the total provitamin A carotenoid content ranged from 789-1770 μg/100g. In 2019, the focus of the project has been on the continuation of the agronomic evaluation, promotion of the developed recipes, training of community members on community-level micropropagation to enable them to continue the multiplication to share planting materials. Further, the focus was on the institutionalization of the cultivars as part of the national germplasm collection for continued and sustainable conservation and future use. Currently, in NARO-Uganda, TARI-Tanzania and ISABU-Burundi, the vitamin A-rich bananas are being integrated into the national banana germplasm collections. In DRC the process is planned for early 2020. The 14-year program has achieved some notable successes, with expanding adoption of five pVAC-rich, tasty cultivars, that perform at least as well as local options, in terms of yield and pest tolerance. The program has also successfully trained tens of thousands of stakeholders in communities across the region, in production practices, nutrition, planting material production, food processing and recipes. During implementation the team better has come to better understand that: i) the adoption of the exotic banana is possible; ii) taste and values vary across regions and communities, so acceptability studies are needed; iii) community resource persons are critical for sustained impact; iv) sustainable access to the planting material is vital; v) farmers must be fully engaged in the evaluation and selection of the materials (agronomic and sensory); vi) dietary studies on nutrient-trade-offs must be conducted; and vii) diet systems differ across countries and regions. Lessons for scaling regionwide adoption of VABs can be drawn from the introduction and scaling of orange-fleshed sweetpotatoes (OFSPs) in sub-Saharan Africa1. A ‘VAB for Profit and Health Initiative (VPHI).’could help reach millions of households across SSA, that builds on the 2019 VAB institutionalisation efforts.